Transport properties of mechanochemically synthesized copper (I) selenide for potential applications in energy conversion and storage - Marcela Achimovičová; Katarína Gáborová; Jiří Navrátil; Petr Levinský; Olha Skurikhina; Juraj Kurimský; Jaroslav Briančin; Tomáš Plecháček; Dáša Drenčaková (Discover Nano, 2024)
Abstract This work studied the thermal stability, electrical, and thermoelectrical properties of copper(I) selenide, Cu2Se synthesized by high-energy milling in a planetary ball mill. The phase composition was investigated by X-ray powder diffraction analysis and scanning electron microscopy. The conversion of the precursors during mechanochemical synthesis and the stability of the product was monitored by thermal analysis. The dependence of electrical properties on the product porosity was observed. For the densification of Cu2Se, the method of spark plasma sintering was applied to prepare suitable samples for thermoelectric characterization. High-temperature thermoelectric properties of synthetic Cu2Se were compared to its natural analogue-mineral berzelianite in terms of its potential application in energy conversion. Based on the results a relatively high figure-of-merit, ZT parameter (~ 1.15, T = 770 K) was obtained for undoped Cu2Se, prepared by rapid mechanochemical reaction (5 min). Cyclic voltammetry measurements of Na/NaClO4/Cu2Se cell implied that mechanochemically synthesized Cu2Se could be used as a promising intercalation electrode for sodium-ion batteries.